Evaluating the Alignment of “Splash 1 Smart Path to Learning English” with Curriculum Standards: A Content Analysis for Indonesian Vocational High Schools - Badrus, Badrus; Jamilah, Jamilah (EDUPEDIA Publisher, 2025)
This study aims to reveal: The quality of the English course book entitled Splash 1 Smart path to Learning English SMK/MAK Grade X (K-Merdeka) based on BSNP. This study is a content analysis with the descriptive-qualitative approach. The analysis procedures consisted developing a concrete research question, connecting it to theory, defining the research design, selecting the sample or material and the sampling strategy, collecting and analyzing the data, and processing the study. The credibility and dependability of this study was gained from consensus and audit trails. The course book analysis in this study considered six criteria proposed by Education National Standarization/Badan Standar Nasional Pendidikan (BSNP). Based on the results and analysis of the study, the course book was categorized as “good” by achieving an average score of 85% of the seven proposed criteria established BSNP. The criteria consist of: the appropriateness of materials with curriculum (90%), the material accuracy (83%), supporting learning materials (80%), presentation technique (85%), teaching and learning technique (80%), and presentation coverage (93%). Considering the results above, so this course book is suitable for use by students at vocational high schools in Indonesia based on the criteria suggested by BSNP. Therefore, the course books can be used as a reference for the teacher to teach the students at vocational high school level